The Endothelium as a Therapeutic Target in Diabetes: A Narrative Review and Perspective - Adams, Jose A.; Uryash, Arkady; Lopez, Jose R.; Sackner, Marvin A. (Frontiers in Physiology, 2021)
Diabetes has reached worldwide epidemic proportions, and threatens to be a significant economic burden to both patients and healthcare systems, and an important driver of cardiovascular mortality and morbidity. Improvement in lifestyle interventions (which includes increase in physical activity via exercise) can reduce diabetes and cardiovascular disease mortality and morbidity. Encouraging a population to increase physical activity and exercise is not a simple feat particularly in individuals with co-morbidities (obesity, heart disease, stroke, peripheral vascular disease, and those with cognitive and physical limitations). Translation of the physiological benefits of exercise within that vulnerable population would be an important step for improving physical activity goals and a stopgap measure to exercise. In large part many of the beneficial effects of exercise are due to the introduction of pulsatile shear stress to the vascular endothelium. Pulsatile Shear Stress (PSS) is a well-known stimulus for endothelial homeostasis, and induction of a myriad of pathways which include vasoreactivity, paracrine/endocrine function, fibrinolysis, inflammation, barrier function and vessel growth and formation. The endothelial cell mediates the balance between vasoconstriction and relaxation via the major vasodilator endothelial derived nitric oxide (eNO). eNO is critical for vasorelaxation, increasing blood flow, and an important signaling molecule that downregulates the inflammatory cascade. A salient feature of diabetes, is endothelial dysfunction which is characterized by a reduction of the bioavailability of vasodilators, particularly nitric oxide (NO). Cellular derangements in diabetes are also related to dysregulation in Ca2+ handling with increased intracellular Ca2+overload, and oxidative stress. PSS increases eNO bioavailability, reduces inflammatory phenotype, decreases intracellular Ca2+ overload, and increases antioxidant capacity. This narrative review and perspective will outline four methods to noninvasively increase PSS; Exercise (the prototype for increasing PSS), Enhanced External Counterpulsation, Whole Body Vibration, Passive Simulated Jogging and its predicate device Whole Body Periodic Acceleration, and will discuss current knowledge on their use in diabetes.